2018
DOI: 10.1002/jrs.5362
|View full text |Cite
|
Sign up to set email alerts
|

Chemical behavior of croconic acid coordinated to Co(II) adsorbed on silver surface

Abstract: The vibrational properties of croconic acid (CA), the associated anionic specie croconate (CR), and their complexes with the transition metals Co(II) were investigated through surface‐enhanced Raman scattering (SERS) spectroscopy. This is the first time the SERS spectra of CA and CR are reported. The normal Raman spectrum of CA after the addition of Co(II) was similar to the corresponding spectrum of CR in the presence of Co(II), suggesting the dissociative coordination of CA with Co(II) cation. Similar behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…The concomitant changes occurring in the 24 h SERS spectrum result in an overall spectrum that also differ from that expected for Cro. [30] The most intense bands are observed at 375, 426, 533, 556, 580, 641, 762, 1086, 1338, 1414, 1470 and 1522 cm -1 . Among the above cited bands, only those at 556 and 641 cm -1 occur at similar position in the SERS spectrum of Cro [30] (see Supporting Material).…”
Section: Methodsmentioning
confidence: 93%
See 4 more Smart Citations
“…The concomitant changes occurring in the 24 h SERS spectrum result in an overall spectrum that also differ from that expected for Cro. [30] The most intense bands are observed at 375, 426, 533, 556, 580, 641, 762, 1086, 1338, 1414, 1470 and 1522 cm -1 . Among the above cited bands, only those at 556 and 641 cm -1 occur at similar position in the SERS spectrum of Cro [30] (see Supporting Material).…”
Section: Methodsmentioning
confidence: 93%
“…This behavior was also seen for croconic acid and it was suggested that the deprotonated oxocarbon species may occur adsorbed on the metallic surface. [30] The pKa values of rhodizonic acid (H 2 C 6 O 6 ), the neutral conjugated basis of Rho containing two hydrogen bonded to two oxygen atoms, has been reported to be 4.37 and 4.66. [41] The SERS results indicate that, in despite of the presence of protonated and deprotonated species in solution, at different proportions in different pHs, there is a deprotonation of the acid in the process of adsorption on AgNP surfaces, even at pH 2, condition that would present ca.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations